Maturation and sex differences in neuromuscular characteristics of youth athletes - DiStefano, L. J.; Martinez, J. C.; Crowley, E.; Matteau, E.; Kerner, M. S.; Boling, M. C.; Nguyen, A. -D.; Trojian, T. H. (The Journal of Strength and Conditioning Research, 2015)
Understanding how neuromuscular factors that are associated with lower extremity injury risk, such as landing kinematics, muscle strength, and flexibility, change as children mature may enhance age-specific recommendations for injury prevention programs. The purpose of this study was to compare these factors in prepubertal, pubertal, and postpubertal male and female athletes. Subjects were classified on maturation stage (prepubertal: 16 males, 15 females, age: 9 ± 1 years; pubertal: 13 males, 12 females, age: 12 ± 3 years; postpubertal: 30 males, 27 females, age: 16 ± 2 years). Researchers measured lower extremity isometric muscle strength and flexibility and evaluated kinematics and vertical ground reaction forces (VGRFs) during a jump-landing task. Three-dimensional kinematics at initial contact (IC), joint displacements, and peak VGRF were calculated. Separate multivariate analyses of variance were performed to evaluate sex and maturation differences (a = 0.05). Postpubertal females landed with less knee flexion at IC (p = 0.006) and demonstrated lower knee extension strength (p = 0.01) than prepubertal and pubertal females. Postpubertal males landed with less hip adduction displacement (postpubertal males = 12.53 ± 6.15°, prepubertal males = 18.84 ± 7.47°; p = 0.04) and less peak VGRF (postpubertal males = 1.53 ± 0.27% body weight [BW], prepubertal males = 1.99 ± 0.32% BW; p = 0.03) compared with prepubertal males. These findings suggest encouraging sagittal plane absorption and decreasing frontal plane motion at the hip, whereas maintaining quadriceps strength may be important for reducing injury risk in postpubertal athletes.